2018
DOI: 10.1186/s13054-018-2167-x
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotics modulate gut microbiota and reduce enteritis and ventilator-associated pneumonia in patients with sepsis: a randomized controlled trial

Abstract: BackgroundCommensal microbiota deteriorate in critically ill patients. The preventive effects of probiotic/synbiotic therapy on microbiota and septic complications have not been thoroughly clarified in patients with sepsis. The objective of this study was to evaluate whether synbiotics have effects on gut microbiota and reduce complications in mechanically ventilated patients with sepsis.MethodsSepsis patients who were mechanically ventilated in the intensive care unit (ICU) were included in this randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
197
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(202 citation statements)
references
References 37 publications
3
197
1
1
Order By: Relevance
“…Probiotics, such as Bifidobacterium bifidum , Streptococcus faecalis and Clostridium butyricum are now available for clinical use, and it is worth considering the use of these probiotics during HSCT. Indeed, a recent report has shown the efficacy of synbiotics containing strains of Bifidobacterium breve and Lactobacillus casei in preventing the incidence of enteritis and pneumonia in patients with septicaemia (Shimizu et al , ). On the other hand, Suez et al () reported that taking probiotics hindered microbiota recovery after antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics, such as Bifidobacterium bifidum , Streptococcus faecalis and Clostridium butyricum are now available for clinical use, and it is worth considering the use of these probiotics during HSCT. Indeed, a recent report has shown the efficacy of synbiotics containing strains of Bifidobacterium breve and Lactobacillus casei in preventing the incidence of enteritis and pneumonia in patients with septicaemia (Shimizu et al , ). On the other hand, Suez et al () reported that taking probiotics hindered microbiota recovery after antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Shimizu et al [96] have also investigated the ability of a synbiotic (Bifidobacterium breve strain Yakult, Lactobacillus casei strain Shirota, and galactooligosaccharides) to reduce complications in VAP and modulate the gut microbiome, confirming a positive effect.…”
Section: Use Of Probiotics In Ventilator-associated Pneumonia (Vap)mentioning
confidence: 98%
“…The use of prebiotics in combination with probiotics, i.e., synbiotics, is limited in critically ill patients, with few published studies [92][93][94][95][96]. A meta-analysis conducted by Manzanares et al [97] analyzed the therapeutic efficacy of four trials with synbiotics versus 10 trials using probiotics, and found no additional benefit of the synbiotics compared to the probiotics alone.…”
Section: Use Of Prebiotics In Critically Ill Patientsmentioning
confidence: 99%
“…the decontamination of the digestive tract (SDD), administration of probiotics and prebiotics alone or in combination (synbiotics), and fecal microbiota transplantation (FMT). 3,16,17 The present study aims to describe the IM profiles in critically ill ICU patients, with and without sepsis, and try to shed light on the role of IM as contributing factor in the evolution of these patients and its influence on ICU stay time, development of different medical complications, and mortality. Additionally, we explored several variables recorded upon ICU admission and stay to determine IM covariates and potential confounding variables in this cohort.…”
Section: Introductionmentioning
confidence: 99%